Ketimpangan Sosial dan Psikologis dalam Interaksi Siswa Berbeda Latar Ekonomi di Lingkungan Kelas - Putri Suci Rahmadani Br Sinurat; Nabila Arbaa Fadhilah; Khoirunnisa Nasution; Nabilla Nabilla; Alberto Siagian; Rafi Arya Dipa Permana; Rahmilawati Ritonga (Politeknik Kampar, 2025)
This study investigates the social and psychological disparities in interactions among elementary school students with different economic backgrounds. Findings reveal that students from higher economic status families display greater confidence, active participation, and leadership in class activities, supported by access to better educational resources. Conversely, students from lower economic status families often exhibit passivity, feelings of inferiority, and limited classroom engagement. These challenges highlight the importance of inclusive teaching practices, such as heterogeneous group activities and equitable recognition by teachers, which can create a supportive learning environment for all students. This qualitative library research emphasizes the role of education in addressing social inequalities.